In Vitro and In Vivo Rat Model Assessments of the Effects of Vonoprazan on the Pharmacokinetics of Venlafaxine - Chen F; Jiang H; Xu J; Wang S; Meng D; Geng P; Dai D; Zhou Q; Zhou Y (Dove Medical Press, 2020)
Feifei Chen,1,* Hui Jiang,1,* Jia Xu,1 Shuanghu Wang,1 Deru Meng,1 Peiwu Geng,1 Dapeng Dai,2 Quan Zhou,1 Yunfang Zhou1 1The Laboratory of Clinical Pharmacy, The Sixth Affiliated Hospital of Wenzhou Medical University, The People’s Hospital of Lishui, Lishui, Zhejiang 323000, People’s Republic of China; 2The Key Laboratory of Geriatrics, Beijing Institute of Geriatrics, Beijing Hospital, National Center of Gerontology, National Health Commission, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing 100730, People’s Republic of China*These authors contributed equally to this work.Correspondence: Yunfang Zhou; Quan ZhouThe Laboratory of Clinical Pharmacy, The Sixth Affiliated Hospital of Wenzhou Medical University, The People’s Hospital of Lishui, Lishui, Zhejiang 323000, People’s Republic of ChinaTel/Fax +86 578 2780081Email zyf2808@lsu.edu.cn; zhouquan1991@lsu.edu.cnPurpose: The purpose of the present study was to investigate the effects of vonoprazan on the pharmacokinetics of venlafaxine in vitro and in vivo.Methods: The mechanism underlying the inhibitory effect of vonoprazan on venlafaxine was investigated using rat liver microsomes. In vitro, the inhibition was evaluated by determining the production of O-desmethylvenlafaxine. Eighteen male Sprague–Dawley rats were randomly divided into three groups: control group, vonoprazan (5 mg/kg) group, and vonoprazan (20 mg/kg) group. A single dose of 20 mg/kg venlafaxine was administrated to rats orally without or with vonoprazan. Plasma was prepared from blood samples collected via the tail vein at different time points and concentrations of venlafaxine and its metabolite, O-desmethylvenlafaxine, were determined by ultra-performance liquid chromatography-tandem mass spectrometry.Results: We observed that vonoprazan could significantly decrease the amount of O-desmethylvenlafaxine (IC50 = 5.544 μM). Vonoprazan inhibited the metabolism of venlafaxine by a mixed inhibition, combining competitive and non-competitive inhibitory mechanisms. Compared with that in the control group (without vonoprazan), the pharmacokinetic parameters of venlafaxine and its metabolite, O-desmethylvenlafaxine, were significantly increased in both 5 and 20 mg/kg vonoprazan groups, with an increase in MRO-desmethylvenlafaxine.Conclusion: Vonoprazan significantly alters the pharmacokinetics of venlafaxine in vitro and in vivo. Further investigations should be conducted to check these effects in humans. Therapeutic drug monitoring of venlafaxine in individuals undergoing venlafaxine maintenance therapy is recommended when vonoprazan is used concomitantly.Keywords: gastroduodenal ulcer, gastroesophageal reflux disease, proton pump inhibitors, vonoprazan fumarate